Visual Culture, Posthumanism and the Pythagorean Paradigm. Documentary vs the Politicization of Truth - Sampanikou, Evi D. (Journal of Posthumanism, 2022)
The paper deals with a documentary narrative of the real story of a philosophical project that came out of a huge accident. The accident at the Chernobyl Nuclear Power Plant in Ukraine, Soviet Union on April 26, 1986. In 1997, seven scientists involved into the accident leave Ukraine for health reasons. They settle on Gavdos, a small island south of Crete, the most distant border of Europe in the Mediterranean. They remain there for about fifteen years and initially have a major positive interaction with the local community, leading a Pythagorean School and several philosophical group meetings, public work, and constructions. During this time, they evolve a new philosophical approach to humanity, the option for immortality, based on what they call “Philosophical Evolution”, a combination of Pythagorean teaching and the ideas of Epicurus, and also specific views that can be related to critical posthumanism and transhumanism.